2017
DOI: 10.1039/c7ra06810g
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-grafted magnetic microspheres for enhanced removal of methylene blue from aqueous solutions

Abstract: Chitosan/magnetite composite microspheres were grafted with polymer by graft polymerization of 2-acrylamido-2-methylpropane sulfonic acid and acrylic acid onto their surface and then applied for the removal of methylene blue from aqueous solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…Compared with other two models, the PSO model correlation coefficients were much closer to 1.0, meanwhile the q value calculated by PSO model is much closer to the actual value. This confirmed that DCFS removal rate was dependent on the quantity of DCFS flocculated onto the surface of TAPAM-PDA-Fe3O4 [36,37]. The PSO model simulated curves of DCFS enrichment kinetics by TAPAM-PDA-Fe3O4 are presented in Figure 10A.…”
Section: Dcfs Enrichment Kinetics Analysissupporting
confidence: 65%
See 1 more Smart Citation
“…Compared with other two models, the PSO model correlation coefficients were much closer to 1.0, meanwhile the q value calculated by PSO model is much closer to the actual value. This confirmed that DCFS removal rate was dependent on the quantity of DCFS flocculated onto the surface of TAPAM-PDA-Fe3O4 [36,37]. The PSO model simulated curves of DCFS enrichment kinetics by TAPAM-PDA-Fe3O4 are presented in Figure 10A.…”
Section: Dcfs Enrichment Kinetics Analysissupporting
confidence: 65%
“…Compared with other two models, the PSO model correlation coefficients were much closer to 1.0, meanwhile the q value calculated by PSO model is much closer to the actual value. This confirmed that DCFS removal rate was dependent on the quantity of DCFS flocculated onto the surface of TAPAM-PDA-Fe 3 O 4 [36,37] Where q e and q max,exp are the enrichment capacity of the magnetic flocculant at equilibrium and the actual maximum enrichment capacity of the magnetic flocculant, respectively. k 1 and k 2 are the rate constant of first-order and second-order flocculation, respectively.…”
Section: Dcfs Enrichment Kinetics Analysissupporting
confidence: 61%
“…Compared to unmodified adsorbents, the adsorption capacities toward Food Yellow 3 and Acid Yellow 23 were considerably enhanced after modification, indicating that the dyes were captured by electrostatic interaction and ion exchange. On the other hand, polymer-grafted magnetic microspheres (GMMs) were prepared by graft polymerization of 2-acrylamido-2-methylpropane sulfonic acid and acrylic acid onto the surface of chitosan/magnetite composite microspheres and were used as an adsorbent to remove methylene blue from aqueous solutions [122]. The authors reported a maximum adsorption capacity for methylene blue of 926 mg g −1 , which is notably higher than the reported values for other adsorbents.…”
Section: Polymer-based Materialsmentioning
confidence: 96%
“…Meanwhile, the biological compatibility of magnetic polymer microsphere surface could be improved by modification of organic functional groups. In recent years, the magnetic polymer microspheres have been developing as novel functional materials . Wang et al reported magnetic poly(styrene‐glycidyl methacrylate) porous microspheres with high magnetic content were prepared by surfactant reverse micelles and emulsion polymerization of monomers, in which the well‐dispersed Fe 3 O 4 nanoparticles were modified by polyethylene glycol and oleic acid respectively.…”
Section: Introductionmentioning
confidence: 99%